Mégalithismes vivants et passés - approches croisées : living and past megalithisms : interwoven approaches - Jeunesse, Christian,; Le Roux, Pierre, 1960-; Boulestin, Bruno, (Archaeopress, 2016)
This volume discusses how the patterns drawn from the observation of 'living' megalithic societies have been used to try and shed light on the functioning of European Neolithic societies.